PICOSEC-Micromegas: Robustness measurements and study of different photocathode materials. (September 2019) - Sohl, L; Bortfeldt, J; Brunbauer, F; David, C; Desforge, D; Fanourakis, G; Franchi, J; Gallinaro, M; García, F; Giomataris, I; González-Díaz, D; Gustavsson, T; et al.
Abstract: Detectors with a time resolution of 20-30 ps and a reliable performance in high particles flux environments are necessary for an accurate vertex separation in future HEP experiments. The PICOSEC-Micromegas detector concept is a Micro-Pattern Gaseous Detector (MPGD) based solution addressing this particular challenge. The PICOSEC-Micromegas concept is based on a Micromegas detector coupled to a Cherenkov radiator and a photocathode. In this detector concept, all primary electrons are initiated in the photocathode and the time jitter fluctuations are reduced. Different resistive anode layers have been tested with the goal of preserving a stable detector operation in a high intensity pion beam. One important characteristic of a gaseous detector in a high flux environment is the ion backflow (IBF). That can cause damage to more fragile photocathode materials like CsI. Various types of photocathode materials have been tested in order to find a robust solution against IBF bombardment.